Brief transcranial focused ultrasound stimulation causes lasting modifications to the synaptic circuitry of the hippocampus - William W. Watts; Benjamin Clennell; James K. Jiang; Konoha Izaki-Lee; Abhishek Binodh; Robyn Cuthell; Deniz Tonyali; Jon Crompton; Rosie Taaffe; Alanoud Alqahtani; Anna Andrieu; Igino Rafael Besinga; et al. (Brain Stimulation)
Background: Brief transcranial focused ultrasound stimulation (tFUS) is used in cognitive mapping, where it is assumed that the intervention itself does not cause lasting modifications to the underlying networks being targeted. However, how so-called ‘offline’ effects impact the dynamic function of neural circuits is largely unknown. Objectives: To determine the persistent effects of ultrasound stimulation on hippocampal circuit function. Methods: Acute rat hippocampal slices in vitro, and rat hippocampi in vivo, were exposed to 40 s, 5 Hz pulsed ultrasound or sham stimulation. The effects of ultrasound on the dynamic synaptic and circuit function of the hippocampus were assessed through quantitative proteomics and extracellular field electrophysiology. Results: We find that ultrasound stimulation induces persistent and differential changes in protein expression and kinase activity in the hippocampus. This occurs concurrently with an enhancement of basal synaptic transmission and modifications to the susceptibility for the hippocampal circuit to undergo synaptic plasticity. These effects occur via a canonical Akt-dependent metaplastic process. Conclusion: The results indicate that tFUS can fundamentally modulate key signalling mechanisms that are responsible for determining the synaptic efficacy in a neural circuit. Importantly, these effects last beyond the duration of the stimulus. These findings provide a mechanistic insight into the sustained impact of tFUS on network function, and emphasise the importance of considering such effects in animal and human studies.